Body Dimensions Of Fulani And Yoruba Ecotype Chickens Under Intensive Systems Of Management (2009)
One hundred and thirty- three (133) day old chicks consisting of sixty-seven (67) Fulani ecotype chicks and sixty-six (66) Yoruba ecotype chicks were used in a 12-weeks study to compare body weight and 10 body parameters of birds under the intensive system of management. Results showed that the Fulani ecotype chicks had better live weight from week 1 - 12 (p>0.05) (live weight: 32.30±3.74 - 461.50±102.06g for females and 34.00±3.73- 552.43±104.98g for males) while the Yoruba ecotype chicks had lower live weights (24.27±1.55¬ 394.46±29.86g for females and 24.09±1.48- 395.92±17.85g for males respectively). The Fulani type also had superior values for breast breadth and length, with values ranging from 2.06±0.37- 11.14±1.49cm for male breast length and 1.92±0.28- 10.45±1.14cm for female breast length. The breast breadth had values of 2.60±0.53- 2.60±0.53cm for males and 2.64±0.49- 8.60±0.99cm for females. The Yoruba ecotype chickens however had superior values (p>0.05) for comb length (0.58±0.9- 2.30±0.37cm for males, 0.62±0.09¬ 1.72±0.19cm) and beak length (1.32±0.11- 2.94±0.13cm for males, 1.27±0.08-2.82±0.16cm for females), throughout the study period. Wing length also changed in the same way from week 7 for females and week 9 for males to favour values recorded for the Yoruba ecotype chickens. All other parameters were higher (p>0.05) for the Fulani ecotype chickens. It was concluded that the Fulani ecotype chicken has potentials to be selected as meat type chickens while the Yoruba ecotype chickens has potentials to be selected more as egg type chickens.